Hopping Conductivity Mechanism in Cd3As2 Films Prepared by Magnetron Sputtering - Glukhov, O. V. (My University, 2020)
Cadmium arsenide films on oxidized silicon substrates were obtained by RF magnetron sputtering. The structure and morphology of the surface were studied by atomic force microscopy (AFM) and Raman spectroscopy (RS). The Raman spectrum contains peaks characteristic for Cd3As2 films at 194, 249, and 303 cm − 1. The carrier mobility in the samples was 0.15-1.7·103 cm2V − 1s − 1 at concentrations of 0.7- 4.4·1019 cm − 3. It has been established that for the sample No 1 in the temperature range T  10-15 K, the variable-range hopping (VRH) conductivity mechanism according to the Mott law is implemented. This can be explained by the fact that a microscopic disorder becomes important for electron localization in this temperature region. This is due to a decrease in temperature or an increase in the degree of disorder. In this case, the jump becomes possible only inside the Mott energy band near the Fermi level. The charge transfer in sample No 2 at T  220-300 K is carried out by the VRH conductivity of the jump over localized states lying in a narrow energy band near the Fermi level. These states can be created by grain boundaries and dislocations. The relations between the values of the Coulomb gap Δ and the zone width of localized states W are consistent with the corresponding conduction mechanism.
Keywords: Cadmium arsenide; Dirac semimetals; Thin films; Hopping conductivity